Mampu Bernaratif dalam Bahasa Indonesia Dikalangan Remaja - Tio Rosalinda S. Pakpahan; Trina Dara Br Sinuraya; Henni Sara Gracia Br Ginting; Lasenna Siallagan (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Narrative ability in the Indonesian language among teenagers is an important topic to investigate, considering the role of language as a tool for communication and cultural expression. This research aims to explore the extent to which teenagers can construct and deliver narratives in Indonesian properly and correctly. The research method used includes surveys and in-depth interviews with a number of teenagers from various educational and social backgrounds. The results indicate that teenagers' narrative abilities are influenced by factors such as the quality of Indonesian language education, the use of social media, and reading habits. The study also found that while many teenagers can create creative and engaging narratives, there are still challenges regarding the correct use of grammar and vocabulary richness. Therefore, further efforts are needed from various parties, including educators and parents, to enhance teenagers' narrative abilities in the Indonesian language.